2021
DOI: 10.1186/s41043-021-00263-w
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes about vitamin D and sunlight exposure in premenopausal women living in Jeddah, and their relationship with serum vitamin D levels

Abstract: Background Saudi women are at risk of vitamin D deficiency because they are fully covered by traditional clothing and because of their indoor lifestyle. The latest national study reported that vitamin D deficiency (serum 25(OH)D < 50 nmol/L) affects 72% of young Saudi women. Because little information is available regarding knowledge on vitamin D, attitudes toward sun exposure, and the vitamin D status of premenopausal women in Jeddah, more research is necessary in order to develop effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 51 publications
(78 reference statements)
2
20
0
1
Order By: Relevance
“…Additionally, sun exposure over the previous week, sunscreen usage, oily fish consumption was not found to be associated with Vit D status among pregnant women [ 48 ]. As for our study and previous research, no statistically significant relationship was found between serum levels and dietary intake of Vit D with knowledge of Vit D, either before, or after adjustment for potential confounder in Saudi premenopausal women [ 49 ]. Interestingly, in a study including 1044 from the general population in Kuwait, 80% of people were found to have adequate knowledge; although Vit D deficiency remained prevalent among them [ 50 ].…”
Section: Discussionsupporting
confidence: 54%
“…Additionally, sun exposure over the previous week, sunscreen usage, oily fish consumption was not found to be associated with Vit D status among pregnant women [ 48 ]. As for our study and previous research, no statistically significant relationship was found between serum levels and dietary intake of Vit D with knowledge of Vit D, either before, or after adjustment for potential confounder in Saudi premenopausal women [ 49 ]. Interestingly, in a study including 1044 from the general population in Kuwait, 80% of people were found to have adequate knowledge; although Vit D deficiency remained prevalent among them [ 50 ].…”
Section: Discussionsupporting
confidence: 54%
“…Regarding socio-demographic data, it was demonstrated that there was no statistically significant relation between osteoporosis and age, social status, education, occupation and smoking. Similarly, Saudi cross-sectional study included premenopausal women reported that no significant association was found between BMD and age, physical activity, parity, and smoking (Zareef et al, 2021). In contrast with an Indian study done by Shatrugna and colleagues ( 2007) included women matched in anthropometric measures, gravidity and calcium intake concluded that occupational activities affect bone mass.…”
Section: Discussionmentioning
confidence: 92%
“…This higher prevalence can be due to inclusion of both premenopausal and postmenopausal women in addition to different population. On the other hand, a Saudi cross-sectional study of premenopausal women aged 20-50 years revealed that osteopenia was in 46.1% of them, with no osteoporosis had been diagnosed by using DEXA scan (Zareef et al, 2021). This difference may be referred to variation in the studied population.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…28,29 This might be attributed to the constant efforts to improve the awareness, knowledge, attitude, and practices towards maintaining normal levels of 25[OH]D among Saudi population. 30,31 Moreover, different populations, assays and definitions of deficiency could influence these results.…”
Section: Discussionmentioning
confidence: 99%